2016
DOI: 10.1007/s11523-016-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hyponatremia and Immune Nephritis Following an Initial Infusion of Nivolumab

Abstract: Anti-programmed cell death-1 (PD-1) antibodies pembrolizumab and nivolumab are becoming increasingly important in the treatment of melanoma and non-small cell lung cancer. These agents are known to induce many immune-related adverse events, but rapid-onset nephritis and immune-related hyponatremia have not been described to date. We describe the case of an adult patient who developed severe hyponatremia and rapid-onset nephritis following the first infusion of nivolumab for metastatic melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Six patients from the nivolumab + reRT cohort were on dexamethasone (range 2-12 mg daily) at start of reRT and all were able to taper steroids at end of reRT. On follow-up MRI [34,35]. The patient was able to complete Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Six patients from the nivolumab + reRT cohort were on dexamethasone (range 2-12 mg daily) at start of reRT and all were able to taper steroids at end of reRT. On follow-up MRI [34,35]. The patient was able to complete Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, one case of interstitial nephritis was also reported in the nivolumab group [9]. Regarding trials in patients with melanoma, both AKI and hyponatremia have been reported [37,38,39,40,41,42,43]. Online supplementary Table 3 summarizes the recent case reports of renal toxicities with this agent.…”
Section: Introductionmentioning
confidence: 97%
“…In the renal tissue, there is upregulation of PD-L1 by renal cells, which will bind and signal through PD-1 expressed by T cells, trying to prevent those cells from proliferating and damaging the tissue. However, when the self-reactive T cells have their PD-1 receptor blocked by the antibody, the PD-1/PD-L1 signaling will be interrupted and T cells will further proliferate and cause cytotoxic injury to the kidney [43]. In addition, PD-L1- and L2-deficient mice have also accelerated ischemic reperfusion renal injury [44].…”
Section: Introductionmentioning
confidence: 99%
“…78 AKI has been reported with both anti−CTLA-4 79 as well as with PD-1/PD-L1 inhibitors. 75,80 A recent meta-analysis that included a total of 11,482 patients reported a 2.3% incidence of AKI associated with the use of PD-1/PD-L1 inhibitors. 81 The combined use of CTLA-4 and PD-1 inhibitor has been reported to be linked to a higher incidence of AKI (5%) as compared with monotherapy.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%